Revitalization Practices of World Cultural Heritage: A Case Study of Yungang Grottoes - Yang, Liran; Singyabuth, Supachai (Journal of Ecohumanism, 2025)
In contemporary society, the consumption of symbols and meanings has become the core of postmodern society, and engaging with cultural heritage has become an important way for people to seek connections with society and represent their own identities. Under the influence of consumerism, cultural heritage has been packaged as consumable goods, transforming into a public history belonging to the market economy. Public history enhances communication across all levels of society and cultural heritage, thereby generating diverse social needs. This process leads to new developments in cultural heritage, transforming the value of existing art, culture, history, and other aspects into economic value for consumption. This is a new social phenomenon that combines art and sociology, and it is also a popular trend in contemporary society. This study takes the Yungang Grottoes as a case, employing field investigation, observation, and literature analysis among qualitative research methods to study the historical consumption forms of World Cultural Heritage in the context of modern society. The study found that World Cultural Heritage contains unique cultural values, and under the influence of historical consumerism, the value system of the heritage is expanded. The rational utilization of heritage becomes the key direction for sustainable development of heritage, enriching the forms of historical consumption of cultural heritage is the key force for the revitalization of cultural heritage. The study has universality and provides important reference value for the revitalization of cultural heritage in other regions of the world.